PF-24 Ringworm on Sapi Bali at Baumata Timur Village - Yohanes TRMR Simarmata; Max Urias Ebenhaizer Sanam; Lucyan Maria Azi Owa Milo (Hemera Zoa, 2018)
Skin is the largest organ in the body, represent 12-14% of the body. Viruses, fungi, algae and parasites are the common cause of skin disorders. The conditions that affect skin are characterized by alopecia, pruritic, dermatitis, and the presence of nodules, crusty lesions or scabs. The main cause of dermatosis or inflammation of the skin in human and many of animal species is dermatophytes, and the infection is called dermatophytosis. The distribution of ringworm is worldwide but the incidence reported frequently in tropical and subtropical countries (Pal, 2017). Ringworm is a keratinophylic fungal disease, highly contagious to humans and caused significant economic consequence to the farmers (Karabulut and Canpolat, 2016). Generally speaking, there are three groups of dermatophytes based on their habitat and host preferences (Akbarmehr, 2011).